Automated ventilator prototype for COVID-19 patient treatment: the design and development of the electronic system - Adrián Stacul; Daniel Pastafiglia; Ariel Dalmas Di Giovanni; Martín Morales; Sergio Saluzzi; Gerardo García (Institute of Advanced Engineering and Science, 2023)
The coronavirus disease 2019 (COVID-19) pandemic has created an urgent global demand for ventilators, respirators and various resuscitation devices. Various research and development organizations, private companies and individual engineers have collaborated and carried out the development of low-cost ventilation prototypes. In turn, doctors and nurses are collapsed due to the exponential increase in COVID-19 cases. This scenario worsens more when the tasks are manual in nature. The article`s objective to describe the electronic system designed, developed and implemented in a functional prototype of an automatic ventilator in order to be evaluated by a team of health professionals to be later used in cases of health emergencies. This system automates the manual ventilation task aided by a few medical resources in a scenario of scarce resources and is a temporary solution when a respirator is not available.